Espansia Club - Fatina, Bakar (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
1 July 2010. Nearly after a year of its existence in Universiti Malaysia Pahang (UMP), 'Espansia' Club, the first Spanish Club was established in June 2010. The name devices from a combination of the word 'Espana' (Spain) and Malesia (Malaysia).